Balancing Act: Navigating Work and Life - A Compelling Bibliographic Exploration Among Women, But Does Everyone Consider It - Endah Susilowati, Nur; Janeusse Fratiwi, Nuzulira; Sri Athena Barus, Carolina (Women, Education, and Social Welfare, 2024)
This bibliographic analysis presents a meticulous exploration of the existing literature regarding women's work-life balance. It synthesizes a wide array of scholarly sources to uncover trends, patterns, and gaps in research on this critical topic. The analysis reveals the myriad challenges women face in their pursuit of work-life balance, ranging from career advancement hurdles to societal expectations and familial responsibilities. It highlights the diverse strategies and coping mechanisms women employ to navigate these challenges successfully. Furthermore, this bibliographic analysis raises the question of whether work-life balance is a universally recognized and prioritized concept among women from various backgrounds and cultures. It critically examines the cultural and contextual factors that may shape differing perspectives on this issue. By scrutinizing the scholarly discourse on women's work-life balance, this analysis aims to provide a comprehensive overview of the current state of knowledge in this field. It offers valuable insights into the research landscape and identifies potential avenues for future investigation, fostering a deeper understanding of the complexities surrounding women's experiences in balancing work and life.